A SAGE approach to discovery of genes involved in autophagic cell death. - Gorski, S.M.; Chittaranjan, S.; Pleasance, E.D.; Freeman, J.D.; Anderson, C.L.; Varhol, R.J.; Coughlin, S.M.; Zuyderduyn, S.D.; Jones, S.J.M.; Marra, M.A. (Current Biology, 2003)
Programmed cell death (PCD), important in normal animal physiology and disease, can be divided into at least two morphological subtypes, including type I, or apoptosis, and type II, or autophagic cell death. While many molecules involved in apoptosis have been discovered and studied intensively during the past decade, autophagic cell death is not well characterized molecularly. Here we report the first comprehensive identification of molecules associated with autophagic cell death during normal metazoan development in vivo. During Drosophila metamorphosis, the larval salivary glands undergo autophagic cell death regulated by a hormonally induced transcriptional cascade. To identify and analyze the genes expressed, we examined wild-type patterns of gene expression in three predeath stages of Drosophila salivary glands using serial analysis of gene expression (SAGE) [7]. 1244 transcripts, including genes involved in autophagy, defense response, cytoskeleton remodeling, noncaspase proteolysis, and apoptosis, were expressed differentially prior to salivary gland death. Mutant expression analysis indicated that several of these genes were regulated by E93, a gene required for salivary gland cell death. Our analyses strongly support both the emerging notion that there is overlap with respect to the molecules involved in autophagic cell death and apoptosis, and that there are important differences.